Developing Immunologically Inert Adeno-Associated Virus (AAV) Vectors for Gene Therapy: Possibilities and Limitations - S. Selot, Ruchita; Hareendran, Sangeetha; R. Jayandharan, Giridhara (Current Pharmaceutical Biotechnology, 2013)
Gene therapy has become a clinical reality as demonstrated by remarkable benefits seen in Phase I/II clinical trials for hemophilia B, lipoprotein lipase deficiency and Leber’s congenital amarousis. The choice of, and the improved understanding in vector characteristics have contributed significantly to this success. The adeno-associated virus (AAV) vectors used in these trials have been long known to be relatively safe and efficacious. However, certain factors, most notably host immunity to the vector, prevent their widespread use. In patients who have pre-existing antibodies to AAV, these vectors will be rapidly cleared. Administration of a relatively high initial dose of vector to achieve and sustain a higher margin of therapeutic benefit is limited by concerns of vector dose-dependent T cell response. Frequent vector administration necessitated by the non-integrating nature of the virus is difficult due to the variable, yet significant host immunological memory. Thus generation of AAV vectors that are immunologically inert is pivotal for the long-term success with this promising vector system. Several strategies, that aim targeted disruption of antigenic sites or those that chemically modify the vectors have been proposed for host immune evasion. While these approaches have been successful in the pre-clinical model systems, this continues to be a field of intense experimentation and constant improvisation due to limited information available on vector immunology or data from human studies. This review forms a comprehensive report on current strategies available to generate immunologically inert AAV vectors and their potential in mediating longterm gene transfer.
Keywords: stealth vector